Estimulación acuática y su incidencia en el desarrollo integral en niños de 1-4 años en la “corporación para sus niños” en la provincia Pichincha cantón Quito parroquia Calderón sector Carcelén en el período 2014-2015 - Carrera Cornejo, Adriana Carolina (2015)
The research was conducted in the "Corporation for their children" during the academic period 2014-2015; with the participation of the children of the corporation, considering the aquatic stimulation is important for an integral development of the children. If the stimulation is made in the first years of life, where the child can have the pleasure and freedom to strengthen his immunological system and in turn improve his lifestyle. For which the principal objetive of the investigation it was make a guide of activities based on aquatic skills adapted for the children from 1 to 4 years that they help to improve and strengthen the potentials of the children of the corporation being a small part of everything what can do the aquatic stimulation, considering that must be guided for a professional who knows the topic. The results of the surveys made to the carers indicate that the wáter contact accompanied of recreative activities will strengthen the confidence, the language, the autoesteem with their parents and their way that surrounds it creating in the children a world of satisfactions, important emotions for the autoesteem in the early infant development.